Exploring Hidden Connections: Endophytic System and Flower Meristem Development of Pilostyles berteroi (Apodanthaceae) and Interaction with Its Host Adesmia trijuga (Fabaceae) - González, Ana María (2024)
Pilostyles, an endoparasitic genus within the Apodanthaceae family, grows inside host stems with flowers and fruits being the only external manifestations. Previous studies of P. berteroi growing on Adesmia trijuga provided limited details of the endophyte and omitted the origin of flowers and sinker structure. This study, using classical methods of optical microscopy applied to the analysis with scanning electron microscopy and confocal laser scanning microscopy, expands the understanding of the P. berteroi/A. trijuga complex. We find that P. berteroi develops isophasically with its host, forming endophytic patches between the host’s secondary phloem cells. The parasitized Adesmia stem’s cambium primarily produces xylem parenchyma, with limited vessel production and halting fiber formation. The radial polarization of endophytic patches led to the formation of floral meristems. Flowers develop endogenously and emerge by the breakthrough of the host stem. Flowers are connected to the host cambium via chimeric sinkers, combining P. berteroi parenchyma and tracheoids with Adesmia vessels. Unlike previous studies that show uniformity among Pilostyles species, our analysis reveals new insights into the structural interaction between P. berteroi and A. trijuga.